COVID-19 vaccine-taking hesitancy among Bangladeshi people: knowledge, perceptions and attitude perspective - Emran Hossain; Jaber Rana; Sayemul Islam; Akhtaruzzaman Khan; Sudipto Chakrobortty; Nishat Sultana Ema; Festus Victor Bekun (Taylor & Francis Group, 2021)
Several novel efforts have been put forth to make a readily available vaccine against the global pandemic of COVID-19. However, there seems to appear vaccine-taking hesitancy among the general people. Against this backdrop, this current study sets to assess the vaccine-taking intention, ways to overcome the vaccine-taking reluctance among Bangladeshi people and explore their knowledge, perceptions, and attitude toward the COVID-19 vaccine. To this end, this study leveraged on a cross-sectional survey, which was consisted of 1377 respondents covering the eight divisions of Bangladesh. The descriptive statistical method and ordinal logistics regression were employed to explore and rationalize our study outlined objectives. Empirical findings revealed that approximately 71% of the respondents had adequate knowledge about the COVID-19 vaccine, whereas 46% of the respondents were willing to be vaccinated against COVID-19 while the rest of the respondents were hesitant to take the vaccine. However, concern about the potential side effects was one of the core reasons for vaccine-taking hesitancy. Assuring the common people about vaccine safety and efficacy, along with easing the registration procedure, can ameliorate people's confidence to get vaccinated. Meanwhile, about 60% of the respondents believed that a vaccine could help Bangladesh win the battle against COVID-19 and will allow back to normal life. Although the government has taken some pragmatic action steps to promote the vaccination rate, it is recommended that the mass vaccination program should be extended to the grassroots level with proper extension community support and easing the registration process.